The Relationship Between Family Support And Children's Anxiety During Hospitalization At Hermina Hospital In Samarinda - Olidiana Chandra Klau; Abd. Rahim; Abdullah; Syaiful Bachri; Sitti Badria; Normalia; Gabriella Delfie Natalia (Nursing Practice Journal, 2026)
Hospitalization is an experience that can cause anxiety in children due to unfamiliar surroundings, medical procedures, and separation from family. Unresolved anxiety can affect the healing process, prolong hospitalization, and cause psychological trauma. Family support plays an important role in helping children adapt during hospital treatment. This study aims to determine the relationship between family support and children's anxiety levels during hospitalization in the pediatric ward of Hermina Hospital in Samarinda, East Kalimantan. This study uses a quantitative design with a correlational descriptive method and a cross-sectional approach. A sample of 44 respondents was selected using purposive sampling according to inclusion criteria. Data were collected through family support questionnaires and child anxiety level questionnaires that had been tested for validity and reliability. Data analysis was performed using correlation tests to determine the relationship between the two variables. The results showed that most respondents received good family support and had mild to moderate anxiety levels. Statistical tests showed a significant relationship between family support and children's anxiety levels during hospitalization (p < 0.05). The better the family support provided, the lower the children's anxiety levels. It was concluded that family support plays an important role in reducing children's anxiety levels during hospitalization. Optimize the family-centered care approach by actively involving families in nursing care. Hospitals are advised to develop policies that support family presence and involvement during the child's treatment. The implications is family-based interventions need to be integrated into pediatric nursing practice to reduce anxiety and improve the quality of care.